Activity-based management in Shell Gabon - Ansari, Shahid Jamal; Bell, Jan (London : Institute of Management Accountants, 2008)
During the 1990's, world events, such as Russia's increased oil production and Asia's economic meltdown, caused excess oil supply and low world prices. This case reports actual efforts by Shell Gabon (SG), a wholly owned subsidiary of Royal Dutch Shell (RDS), a major Dutch oil company, to control its costs during that time period in order to obtain necessary funding for capital expenditures.By 1996, most of the oil on land in SG's region was depleted, and the number of barrels produced had decreased without a corresponding reduction in operating costs. Accordingly, the unit operating cost per barrel (UOC) increased. SG needed capital development funds from RDS to expand off shore operations. However, in its peer comparison, SG had one of the highest UOC and was told that they had a low priority for new capital expenditures. Faced with the prospect of decreasing output and increasing UOC, SG used activity based analysis and management to manage cost.While the Case has seven listed requirements, there are three which should be noted. Requirement 2 requires the computation of the cost of activities in the IT Department; requirement 3 deals with appropriate performance measures and requirements 5 and 6 deal with benchmarking. These requirements will be of interest to readers, especially since the case is unusual - it is set in the oil industry and deals with a service department.
Originally published in Ansari, S., & Bell, J. (2008). Activity-Based Management in Shell Gabon. IMA Education Case Journal, 1(4), Article 4.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Shell-Gabon.; Petroleum industry and trade -- Gabon -- Cost of operation; Petroleum industry and trade -- Finance -- Gabon; Risk assessment